Exploring Constituent Structure through Elliptical Sentences in the Witches Novel by Roald Dahl - Luh Herma Risthayani; Putu Devi Maharani (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
The phenomenon of elliptical sentence in the communication is an effective way to avoid the redundance, highlight the important information, and make a concise and clear context. The process of deleting the sentence constituent is observed through the theory that proposed by Kiss and Alexiadou (2015). This research investigates the elliptical phenomenon found in a novel entitled The Witches written by Roald Dahl that originally published in 1983 with 208 total pages. The total data that found in this research is 130 data out of all types consist of 12 data (9%) of VP-ellipsis, 9 data (7%) of sluicing, 35 data (27%) of NP-ellipsis, 34 data (26%) of fragment answer, 8 data (6%) of stripping, 2 data (2%) of gapping, 5 data (4%) of pseudogapping, 10 data (8%) of modal complement ellipsis, and 15 data (11%) of null complement anaphora. The highest occurrence in this study is NP-ellipsis with 27% out of 130 total data. Because there are a lot of sentences that specifically omitted in the noun phrase constituent.